Biologische Verbindungen zwischen den Rotbarschbeständen Westgrönlands und der Irmingersee - Kosswig, K. (1996)
Two redfish species are expected to live off western Greenland in a broad distribution area. Except for a small population of adults in the Godthab Fjord, only juvenile and adolescent specimens have been met there, tending to increase in age from the north to the south. As taxonomic identification of single specimens is difficult the distribution of species stocks cannot be clearly identified. This paper deals with spawning areas, migration and drifting routes around Greenland respectively in relation to distributional pattern of juvenile redfish off western Greenland.